6 - Globalisation, ICTs, and the New Imperialism: Perspectives on Africa in the Global Electronic Village: DOI: 10.4314/ad.v30i1.22215 - Ya’u, Yunusa Z. (Africa Development, 2005)
Globalization as promoted by the World Trade Organization (WTO) is resulting in a new imperialism that is characterized by knowledge dependence and the shrinking of the national space for decision making. It is facilitated by information and communication technologies (ICTs). The centrality of ICTs to globalization has resulted in an international concern for bridging the unequal access to ICTs that has come to be termed as digital divide. However, the discourse about bridging the digital divide tends to mask the reality of the digital deficit which is the consequence of a wider development divide. Yet the reality is that the marginality of Africa cannot be addressed by isolationism as a counterforce to globalization. What is needed is to rethink the terms and nature of Africa's integration in the global economy. This means interrogating among others, the current discourse about bridging the digital divide. This contribution addresses the substantive nature of the new imperialism and offers explanation as to why the digital divide tends to increase rather than decrease in spite of the various efforts aimed at closing it. It concludes by offering some directions in which the digital deficit as part of the wider development divide can be addressed.